OPPORTUNITIES FOR EARLY DIAGNOSIS BASED ON BIOMARKERS IN CLINICAL DIAGNOSTIC LABORATORIES: EXPERIENCE AND PROSPECTS OF UZBEKISTAN (Modern American Journal of Medical and Health Sciences, 2025)
This article analyzes the theoretical and practical aspects of early diagnosis based on biomarkers in clinical diagnostic laboratories. The experience of using biomarkers in the diagnosis of cardiovascular, oncological, and infectious diseases was studied in the conditions of Uzbekistan. The results of diagnostic methods based on markers such as troponin, BNP, PSA, CA-125, CEA used in medical institutions of the republic were evaluated based on scientific sources. The prospects for introducing modern molecular and genetic diagnostic technologies into laboratory practice are also highlighted. The study indicates existing infrastructural problems, human resources, and technological gaps, and makes proposals for areas that should be implemented in the future.